A Fully Guided Sequential Template Immediate Loading Protocol for Dual-Arch Implant Surgery - Alruhailie L; Zaidan A; Alasmari A; Raffa O (Dove Medical Press, 2024)
Lamia Alruhailie,1,* Aliyaa Zaidan,2,* Abeer Alasmari,2,* Ossama Raffa1,* 1Department of Prosthodontics, King Abdulaziz Medical City, Jeddah, Saudi Arabia; 2Department of Periodontics, King Abdulaziz Medical City, Jeddah, Saudi Arabia*These authors contributed equally to this workCorrespondence: Ossama Raffa, Department of Prosthodontics, King Abdulaziz Medical City, Jeddah, Saudi Arabia, Tel +966543322668, Email raffa.ossama@gmail.comAbstract: A method is described for designing, fabricating and implementing sequential template immediate loading protocols for dual arch implant therapy. A 41-year-old medically-free patient with terminal dentition was treated following stackable guide loading protocols for maxillary and mandibular arches. Implants were placed following extractions and immediately loaded with full arch fixed prostheses. Healing was uneventful and all implants integrated successfully. Special consideration was given to the design and clinical challenges when implementing stackable guide protocols for dual arch implant therapy.Keywords: prosthodontics, implants, digital dentistry, stackable guides